Multi-year gradient measurements of sea spray fluxes over the Baltic Sea and the North Atlantic Ocean - Markuszewski P.; Nilsson E. D.; Zinke J.; Mårtensson E. M.; Salter M.; Makuch P.; Kitowska M.; Niedźwiecka-Wróbel I.; Drozdowska V.; Lis D.; Petelski T.; Ferrero L.; et al. (Atmospheric Chemistry and Physics, 2024)
Ship-based measurements of sea spray aerosol (SSA) gradient fluxes in the size range of 0.5-47 mu m in diameter were conducted between 2009-2017 in both the Baltic Sea and the North Atlantic Ocean. Measured total SSA fluxes varied between 8.9 x 103 +/- 6.8 x 105 m-2 s-1 for the Baltic Sea and 1.0 x 104 +/- 105 m-2 s-1 for the Atlantic Ocean. The analysis uncovered a significant decrease (by a factor of 2.2 in the wind speed range of 10.5-14.5 m s-1) in SSA fluxes, with chlorophyll a (chl a) concentration higher than 3.5 mg m-3 in the Baltic Sea area. We found statistically significant correlations for both regions of interest between SSA fluxes and various environmental factors, including wind speed, wind acceleration, wave age, significant wave height, and wave Reynolds number. Our findings indicate that higher chl a concentrations are associated with reduced SSA fluxes at higher wind speeds in the Baltic Sea, while the influence of wave age showed higher aerosol emissions in the Baltic Sea for younger waves compared to the Atlantic Ocean. These insights underscore the complex interplay between biological activity and physical dynamics in regulating SSA emissions. Additionally, in both measurement regions, we observed weak correlations between SSA fluxes and air and water temperature and between SSA fluxes and atmospheric stability. Comparing the Baltic Sea and the North Atlantic, we noted distinct emission behaviors, with higher emissions in the Baltic Sea at low wave age values compared to the Atlantic Ocean. This study represents the first comparative analysis of SSA flux measurements using the same methodology in these contrasting marine environments.